Employees’ loyalty towards Research International (M) Sdn. Bhd. / Fadhli Roslan - Roslan, Fadhli (Faculty of Business and Management, 2010)
This study was carried out to determine the level of employees’ loyalty in Research International (M) Sdn Bhd. The researcher collects the information directly from primary source (questionnaires), and the web. The overall findings of the study indicate that the level of employees’ loyalty in RI differ according to departments, which shows that there are some dissatisfaction occurred among employees within the organization. From the study, the researcher had identified several problems arise such as discrimination, peer to peer relationship, leadership issue, the work itself, and lack of motivation factors. In conclusion, some suggestions and strategies have been made to minimize the problems occurred in the organization. This is very crucial for it will affect the engagement level of the organization.